Web 2.0 as a Potential for Development of Young People - Soleša, Dragan; Rajsman, Marijan; Juričić, Vedran (2014)
The research aims to determine how well today's students know and use Web 2.0 architecture as well as why they use applications based on Web 2.0 architecture. The sample in this study consisted of 103 students of both sexes, aged 20 -30 on two faculties and two stud programs. The research was conducted using questionnaires as a research technique in which Web 2.o was investigated by the indicators of computer, information and communication aspects.
ENG